Socio economic and political bases of the Nahdlatul Ulama elite - Marijan, Kacung (The Indonesian quarterly, 1998)
The article examines the socio-economic and political bases which are assumed to be the sources of support and influence for the Nahdlatul Ulama (NU; a traditional Islamic organization which commands the support of some 30 million Indonesian Muslims.) It points out that resources for the NU elites are basically similar to the resources used by other elites in general. (DÜI-Sen)